Didactic sequence based on research-based teaching for microbiology classes in High School (Research, Society and Development, 2024)
The lack of resources and equipment in public schools leads to unidirectional teaching centered on the teacher, and results in low interest on the part of students in the area of Science. The COVID-19 pandemic has driven the need for scientific literacy in society, especially among school-age individuals. The purpose of this study is to focus on improving high school students' scientific literacy in microbiology through inquiry-based teaching by presenting a low to medium cost option for presenting hands-on Microbiology classes. Two experiments were carried out in high school evening classes in Rio de Janeiro, using an investigation-based teaching approach with practical activities, using a semester in basic culture environments. The results indicated that this methodology involved students, making them protagonists of learning, allowing them to explore microbiological concepts in a practical and accessible way, making the content more attractive. Therefore, the study demonstrates the effectiveness of inquiry-based teaching approaches in teaching microbiology in secondary education, emphasizing the importance of interactive and hands-on methods to improve student understanding and engagement.